Analysis of Transient and Steady-State Response in First and Second-Order DC Motor Systems - Ary Pratama Paluga (Journal of Marine Electrical and Electronic Technology, 2025)
DC motor is a fundamental component in various industrial applications due to its controllable dynamic response. However, accurate control of motor behavior, particularly its transient and steady-state response, requires detailed modeling and analysis. The main challenge lies in predicting the performance of first-order and second-order systems under different input conditions and control techniques. This research aims to analyze and compare the transient response and steady-state characteristics of first and second-order DC motor models, focusing on performance indicators such as rise time, settling time, overshoot, and steady-state error. Additionally, this study investigates the effects of PID controller tuning on improving the response of second-order systems. The core contribution of this paper is a structured approach to modeling DC motors as simplified first and second-order systems based on physical parameters extracted from datasheets. Each system model is simulated in MATLAB/Simulink, both in open-loop and closed-loop conditions. For the second-order system, a PID controller is designed using Ziegler-Nichols tuning rules to optimize performance. The analysis shows that the first-order system exhibits smoother but slower response, while the second-order model introduces oscillation but allows for faster regulation when controlled appropriately. Simulation results demonstrate that applying the PID controller reduces overshoot by 70% and shortens the settling time by over 50% compared to the uncontrolled system. In conclusion, both models provide useful insights depending on system design needs. The inclusion of control strategy significantly enhances performance in second-order systems, making them suitable for real-time, dynamic industrial control applications. The findings encourage a system-level understanding of motor dynamics and the critical role of controller design in performance optimization.